Design and Examination of Yogurt Maker Machine with Sensor Temperature DS18B20 - Yunita, Dewi; Nurazis, Alfi Syahri; Juanda, Juanda; Nasution, Indera Sakti; Satriana, Satriana (The University of Lampung, 2024)
Many commercial yogurt brands do not have a minimum total lactic acid bacteria count (107 CFU/g) due to long distribution with inappropriate storage condition. This leads local producers to produce yogurt. However, commercial yogurt maker machines commonly have a low capacity of 0.5 to 2 L. This study aims to design a yogurt maker machine with a capacity of 15 L with a temperature setting of 37 – 45 ℃. The design and flow system were conducted by arranging the electronic components consisting of 5V 4 channel relay, ESP32 module, DS18B20 temperature sensor, RTC, 12V fan (along with 12 VDC connecting components), 220V heater, 20×4 LCD and plugs (adapter) 220 VAC cable. The yogurt maker machine was evaluated for accuracy of temperature readings (DS18B20 sensor and thermometer), response to incubation time and plain yogurt making. The T-Test was used to compare the differences between the two types of sensors measuring instruments. The results showed that the accuracy of temperature readings using the DS18B20 sensor was better than a thermometer, with a distance scale of 0.35-0.75 ℃ (P-value ≤ 0.05). Temperature testing using milk can be carried out with a temperature range of 37-45 ℃ for 12 h. Keywords: DS18B20, Temperature, Yogurt maker machine, Sensors